Peran Senam Jantung Sebagai Upaya Penurunan Tekanan Darah pada Lansia Hipertensi - Ledia Restipa; Syafitri, Rika (Universitas Alifah Padang, 2025)
Hypertension is a condition where systolic blood pressure increases above normal, which is more than 140 mmHg and diastolic blood pressure is more than 90 mmHg. The incidence of hypertension at Andalas Health Center, Padang City was 505 cases in the last two months from January to February. Currently, non-pharmacological treatment is very popular among the community, one of which is heart gymnastics. The purpose of this community service is to determine the effect of heart gymnastics on blood pressure in elderly hypertensives. The activity involved measuring blood pressure before the intervention, showing a cardiac exercise video prior to the elderly participants performing the exercise, measuring blood pressure after the intervention, and distributing educational leaflets.The results of the study were obtained before heart gymnastics, the average blood pressure was 140/90 mmHg. The average blood pressure after 140/80 mmHg, the p-value of 0.000 means that there is an effect of blood pressure before and after heart gymnastics. Based on the results that have been carried out, it is recommended to carry out community service on other non-pharmacological therapies such as (heart gymnastics or traditional types and others) to overcome the problem of changes in blood pressure in hypertensive patients.